Young men in uncertain times - Amit, Vered, 1955-; Dyck, Noel (Berghahn Books, 2012)
Anthropology is particularly well suited to explore the contemporary predicament in the coming of age of young men. Its grounded and comparative empiricism provides the opportunity to move beyond statistics, moral panics, or gender stereotypes in order to explore specific aspects of life course transitions, as well as the similar or divergent barriers or opportunities that young men in different parts of the world face. Yet, effective contextualization and comparison cannot be achieved by looking at male youths in isolation. This volume undertakes to contextualize male youths' circumstances and to learn about their lives, perspectives, and actions, and in turn illuminates the larger structures and processes that mediate the experiences entailed in becoming young men. The situation of male youths provides an important vantage point from which to consider broader social transformations and continuities. By paying careful attention to these contexts, we achieve a better understanding of the current influences encountered and acted upon by young people.